2010
DOI: 10.1002/ppp.689
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost thermal state in the polar Northern Hemisphere during the international polar year 2007–2009: a synthesis

Abstract: The permafrost monitoring network in the polar regions of the Northern Hemisphere was enhanced during the International Polar Year (IPY), and new information on permafrost thermal state was collected for regions where there was little available. This augmented monitoring network is an important legacy of the IPY, as is the updated baseline of current permafrost conditions against which future changes may be measured. Within the Northern Hemisphere polar region, ground temperatures are currently being measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
521
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 687 publications
(535 citation statements)
references
References 26 publications
13
521
1
Order By: Relevance
“…Lütschg et al, 2008), while Engelhardt et al (2010) showed that differences in the timing of a thick snow cover have a similar influence on ground temperature as different forcing climate scenarios. Recently, Christiansen et al (2010) and Romanovsky et al (2010b) demonstrated the large differences of nearsurface ground temperatures between two adjacent boreholes with different snow cover in Svalbard. Deeper ground temperatures will, however, become more similar because of the lateral heat transfer, causing temperatures at greater depths to be integrated over larger surface areas.…”
Section: Uncertainties and Sensitivitymentioning
confidence: 99%
“…Lütschg et al, 2008), while Engelhardt et al (2010) showed that differences in the timing of a thick snow cover have a similar influence on ground temperature as different forcing climate scenarios. Recently, Christiansen et al (2010) and Romanovsky et al (2010b) demonstrated the large differences of nearsurface ground temperatures between two adjacent boreholes with different snow cover in Svalbard. Deeper ground temperatures will, however, become more similar because of the lateral heat transfer, causing temperatures at greater depths to be integrated over larger surface areas.…”
Section: Uncertainties and Sensitivitymentioning
confidence: 99%
“…Deposits of the Holocene cover exposed on top of the Ice Complex unit consist of brownish-black, cryoturbated silty sand with numerous small peat inclusions and are characterized by smaller ice wedges. Deposits of thermokarst depressions are composed of cryoturbated silty sands, numerous plant remains, and peat inclusions, and contain syn- genetic ice wedges about 3 to 5 m wide (Schirrmeister et al, 2003).…”
Section: Study Area and Regional Settingmentioning
confidence: 99%
“…According to Schirrmeister et al (2003) and Wetterich et al (2008) we assume that the average boundary between Ice Complex deposits and underlying fluvial sands lies between 15 and 20 m a.r.l. For calculation purposes in the GIS we set the height of the boundary to 17 m a.s.l.…”
Section: Relief Analyses On Kurungnakh Islandmentioning
confidence: 99%
See 2 more Smart Citations